Musikalisasi Puisi “Hatiku Selembar Daun” - Royke B. Koapaha; Umilia Rokhani; Nurul Farida (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2009)
The musical poem of “Hatiku Selembar Daun”. Music and poetry have a signifi cant relationship; they bothhave an element of sound. This study discusses the relation of the transformation of poetry to musical poem in“Hatiku Selembar Daun” by Djoko Damono Sapardi. The study was conducted by means of the form of music andharmony through musicological studies, as well as the relationship between music and poetry in a musical poemitself. Based on the analysis we concluded that the dominant harmonious relationship between music and the meaningof the poem “Hatiku Selembar Daun” deals with the creative elements in it.